Sports business management decision making around the globe - Foster, George 1948-; O'Reilly, Norm 1973-; Davila, Antonio (Routledge, 2021)
This new edition of a widely adopted textbook equips students with a comprehensive understanding of the sport industry. With a focus on management, strategy, marketing, and finance, the decision-making approach of the book emphasizes key concepts while translating them into practice. Content specific to each of the vital stakeholders in the sport business is included. Foster, O'Reilly, and Dacuteavila present a set of modular chapters supported with international examples, mini-cases, and exercises to help students apply the decision-making approach to real-world situations, involving organizations such as the Olympic Games, FIFA World Cup, the European Premier Leagues and Major North American Professional Sport Leagues. Harvard/Stanford cases are updated for the second edition, and entirely new chapters cover the latest topics, including eSports and Fantasy sport, outside-of-venue revenue streams, and crisis management. This is an ideal textbook for upper-level undergraduate and postgraduate students of sports business and management, supported by a fully updated companion website featuring PowerPoint slides, test questions, teaching notes, and other tools for instructors